Studies on Production and Chemical Property of Singlet Oxygen and Superoxide Radical by Dyestuffs - Vikesh Kumar; M. R. Tripathi; Manish Kumar; Gopal Shukla; Sarvesh Dwivedi; Vandana Sharma (E-Journal of Chemistry)
There are several low lying singlet oxygen (1O2) and superoxide radical (O-2) which are important in photochemical oxidation. In our present analysis we are studying chemical property of singlet oxygen (1O2) and super oxide radical (O-2) and some dyestuffs species to produce reactive oxygen such as singlet oxygen 1O2 and superoxide radicals. Irradiation with sun light in vitro the dyestuff like benzanthrone, metanil yellow and p-aminodiphenylamine were found to produce reactive oxygen species such as singlet oxygen (1O2) and/or superoxide radicals (O-2) .The dose response relationship between singlet 1O2 production when sunlight expose of those dyestuffs (0-25 min), and (0-12 min) for super oxide (O-2) production were studied. However benzanthrone produces detectable amount of 1O2, Although metanil yellow and p-aminodiphenylamine (p-ADPA) did not produce detectable amounts of 1O2 under similar conditions. The above dye stuffs are routinely used in textiles, cosmetics, detergents, leather industries as well as food additives and role of these activated oxygen species in the development of skin diseases.